ANALISIS PERBANDINGAN PROTOKOL JARINGAN DARI SEGI KINERJA DAN KEAMANANNYA PADA FKIP UNTIRTA - Ariwibowo, Didik; Turangga, Rollis Kurnia; Rimanada, Talitha Naurah; Oktiana, Nur Rohima; Wibowo, Adam Falrain; Fahreza, Dzikri; Galih, Muhammad Raihan; Nurfirdaus, Anas; Fauzi, Muhamad Luthfi (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
Research and Evaluation of security system changes from SSO to open systems are important to protect data. Because the increasing cyber threats make this research crucial. Infrastructure Needs to Improve network capacity for many users are a priority. Explore the impact of system changes on information protection. Understanding bottlenecks can help design better infrastructure. The results of the study can be used to improve network policies. Analyze system transitions in specific environments. and Collect user and IT staff perspectives. Use historical data to review bottleneck incidents and data leaks. Open systems reduce administrative burden but increase the risk of unauthorized access. Bottleneck Bottleneck incidents highlight the need for infrastructure upgrades. SSO security is more secure but more expensive and complex. Recommendations Routine maintenance and capacity upgrades are needed for network security and efficiency.